Comparative efficacy of Phyllanthus niruri L. and cotrimoxazole in the treatment of skin infection caused by Staphylococcus aureus. - Praseno, Praseno (Universitas Gadjah Mada, 2001)
Background: Traditional medicine has been widely used in our community and many of them were found to be effective in the treatment of various diseases. Previous studies showed that Phyllanthus niruri L. has an effect as immunostimulator and antiviral activities.Objective: The aim of this study was to evaluate the efficacy of Phyllanthus niruri L. in the treatment of skin infection caused by Staphylococcus aureus.Materials and Methods: Thirty mice of Swiss strain were infected with 2x100 colony forming unit of S.aureus subcutaneously. The mice were then devided into 3 groups; Phyllanthus niruri L.-treated group, cotrimoxazole-treated group, and control group. Treatmen